Governing enclosure for coastal communities: Social embeddedness in a Canadian shrimp fishery. (November 2015) - Foley, Paul; Mather, Charles; Neis, Barbara
Abstract: Critical analyses of neoliberalism׳s influence on fisheries governance have documented how enclosure, quota leasing and renting, and commodification can precipitate negative social consequences for fishing communities. By contrast, this paper draws on the concept of embeddedness to argue that certain policies and social relations can regulate enclosure, quota renting, and commodification in ways that empower community-based groups to facilitate the anchoring of fishery resources and wealth in coastal communities. It does so through an analysis of northern shrimp fisheries in Newfoundland and Labrador, Canada, between the 1970s and the early 2000s. This case study illustrates how fisheries enclosure policies informed by geographically and morally defined principles of access and equity and limits on commodification can meaningfully embed fishery resources and benefits in rural and remote coastal regions that depend on small-scale fishing. Although the application of social principles continues to be marginalized in the context of neoliberal policy regimes that privilege individual economic efficiency over distributive concerns, this paper provides new insight into the conditions under which principles of ethical allocation and distribution of resources are able to persist through an era of neoliberalism. Highlights: Investigates policy approaches that contrast with neoliberal approaches. Examines the application of principles of equity and distribution. Assesses three rural regions where catch share benefits are managed collectively. Shows how enclosure processes can be regulated to benefit small-scale fisheries. Uses the concept of embeddedness to explain findings.